Konstruksi Pendidikan Karakter Religius Berbasis Kegiatan Keagamaan pada Sekolah Islam Terpadu di Kota Palembang - Andesta, Dewi Putri (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
As a response to the importance of strengthening religious values among students, this study explores the construction of religious character education based on religious activities. This study aims to explore the construction of religious character education based on religious activities in Integrated Islamic Schools in Palembang City. The focus of this research is to understand how religious characters are formed through various religious activities in schools, as well as to analyze the contribution of internal and external factors in shaping these characters. This research will also evaluate the extent to which religious activities play a role in the preservation and development of students' religious character. This research uses a qualitative approach. The type of research used in this research is a case study. Data collection through interviews, observation, and documentation. The results of this study indicate that the construction of the religious character of students in Integrated Islamic Schools in Palembang city is successful. This is indicated by a significant increase in the religious character of students which is not only reflected in the school environment but also in everyday life. In implementing religious character education based on religious activities, there are many factors that influence both internal and external factors. Internal factors such as support and school systems, as well as external factors such as cooperation with institutions and parents, play an important role in the success of the formation of students' religious character. Religious activities organized by integrated Islamic schools emphasize moral values such as honesty, simplicity, and compassion. Improving discipline and responsibility, developing empathy and social care, managing emotions and mental resilience, and instilling ethics and principles of life. Abstrak Sebagai respons terhadap pentingnya penguatan nilai-nilai religius di kalangan pelajar, penelitian ini mengeksplorasi konstruksi pendidikan karakter religius berbasis kegiatan keagamaan. Penelitian ini bertujuan untuk mengeksplorasi konstruksi pendidikan karakter religius berbasis kegiatan keagamaan di Sekolah Islam Terpadu di Kota Palembang. Fokus penelitian ini adalah untuk memahami bagaimana karakter religius dibentuk melalui berbagai kegiatan keagamaan di sekolah, serta untuk menganalisis kontribusi faktor internal dan eksternal dalam membentuk karakter tersebut. Penelitian ini juga akan mengevaluasi sejauh mana kegiatan keagamaan berperan dalam pelestarian dan pengembangan karakter religius peserta didik. Penelitian ini menggunakan pendekatan kualitatif. Jenis penelitian yang digunakan dalam penelitian ini adalah studi kasus. Pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa konstruksi karakter religius peserta didik di Sekolah Islam Terpadu di kota Palembang berhasil. Hal ini ditunjukkan dengan adanya peningkatan signifikan karakter religius peserta didik yang tidak hanya tercermin di lingkungan sekolah tetapi juga dalam kehidupan sehari-hari. Dalam mengimplementasikan pendidikan karakter religius berbasis kegiatan keagamaan banyak faktor yang mempengaruhi baik dari dalam dan luar. Faktor internal seperti dukungan dan sistem sekolah, serta faktor eksternal seperti kerjasama dengan lembaga dan orang tua, berperan penting dalam keberhasilan pembentukan karakter religius peserta didik. Kegiatan keagamaan yang diselenggarakan sekolah islam terpadu lebih menekankan nilai-nilai moral seperti kejujuran, kesederhanaan, dan kasih sayang. Peningkatan disiplin dan tanggung jawab, pengembangan empati dan kepedulian sosial, pengelolaan emosi dan ketahanan mental, serta penanaman etika dan prinsip hidup.